Analisis Strategi Penerjemahan 外来語 (Gairaigo) pada Media Sosial Konsulat Jepang di Makassar - Simangunsong, Sampson Trimein; Kasmawati, Kasmawati (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2025)
The use of gairaigo (外来語), or foreign loanwords, has become an increasingly prominent feature in the Japanese language, especially in institutional digital communication. This study investigated the translation strategies applied to gairaigo in the social media posts of the Japanese Consulate in Makassar from 2017 to 2024, employing Peter Newmark’s theory of translation procedures. The research aimed to reveal why gairaigo was frequently chosen over native Japanese vocabulary (wago and kango) in official digital communication and how this choice reflected the evolving needs of digital public diplomacy. Using a qualitative descriptive approach, the study analyzed seven representative Indonesian–Japanese text pairs selected from 130 social media posts after filtering for repetition. The analysis identified the use of multiple translation procedures, including naturalization, transference, transposition, descriptive equivalence, reduction, and free translation. These strategies demonstrated a deliberate adaptation to the stylistic demands of social media, such as informality, brevity, and accessibility for younger audiences. The findings showed that the use of gairaigo in institutional digital diplomacy served not only linguistic but also communicative and cultural functions, shaping both the institutional voice and cross-cultural understanding. This study contributed to translation studies by highlighting the interplay between lexical choice, digital institutional communication, and the pragmatic demands of public diplomacy in a globalized context.